2020
DOI: 10.3390/s20185317
|View full text |Cite
|
Sign up to set email alerts
|

Effect of an Inflatable Air Mattress with Variable Rigidity on Sleep Quality

Abstract: Several studies, wherein the structure or rigidity of a mattress was varied, have been conducted to improve sleep quality. These studies investigated the effect of variation in the surface characteristics of mattresses on sleep quality. The present study developed a mattress whose rigidity can be varied by controlling the amount of air in its air cells. To investigate the effect of the variable rigidity of the air mattress on sleep quality, participants (Male, Age: 23.9 ± 2.74, BMI: 23.3 ± 1.60) were instructe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 74 publications
(81 reference statements)
1
7
0
Order By: Relevance
“…We found that compared to baseline, sleeping on the grid mattress resulted in significant improvements in nighttime sleep quality/quantity and pain, as well as corresponding improvements in daytime mood (i.e., tension, anger, vigor, fatigue, and confusion), perceived stress, daytime fatigue, and pain. Consistent with other research, the mattress is an important environmental component that can improved sleep quality, with mattress firmness being a key aspect 24 …”
Section: Discussionsupporting
confidence: 84%
“…We found that compared to baseline, sleeping on the grid mattress resulted in significant improvements in nighttime sleep quality/quantity and pain, as well as corresponding improvements in daytime mood (i.e., tension, anger, vigor, fatigue, and confusion), perceived stress, daytime fatigue, and pain. Consistent with other research, the mattress is an important environmental component that can improved sleep quality, with mattress firmness being a key aspect 24 …”
Section: Discussionsupporting
confidence: 84%
“…As the number of N1 epochs is insufficient, the prediction probability of the N1 stage was still low, and the proposed model could not learn features of sleep spindle or k-complex separately. Therefore, for future works, we need to improve the performance of the N1 scoring using a rule-based method which reflects the N1 and N2 stage transition probability [50] or oversamples augmenting N1 epochs [51]. Also, the proposed model could be improved in performance by detecting the sleep spindle or k-complex and extracting features in future works.…”
Section: Discussionmentioning
confidence: 99%
“…Such zoned mattresses are commonly divided into ~3–10 parts according to the body contours, and the influence of zoned mattresses on sleep tends to vary by group. Varying the support pressure of the shoulder and hip of the mattress would improve sleep (Baek et al, 2022 ), especially for poor sleepers (Yu et al, 2020 ). A previous study using a zoned spring mattress (Verhaert et al, 2011 ) indicated that suitable support improved the sleep quality for the participants who spent most of the time in a lateral or prone posture.…”
Section: Introductionmentioning
confidence: 99%